Biodiversity Conservation in Road Projects : Lessons from World Bank Experience in Latin America - Ledec, George; Posas, Paula J. (World Bank, Washington, DC, 2017)
The unprecedented and irreversible loss of biodiversity in modern times is caused primarily by the elimination or degradation of natural habitats around the world. Since the construction and improvement of roads sometimes leads, directly or indirectly, to the loss and degradation of natural habitats, road construction and biodiversity aims are often at odds. However, many potentially serious conflicts between road projects and biodiversity conservation can be avoided. Induced negative impacts of road projects on biodiversity can be minimized by careful project siting, taking special care to avoid passing through protected areas and other critical natural habitats, including forested areas (which are especially vulnerable to induced impacts). Where some natural habitat loss is inevitable, appropriate mitigation may include the establishment of strict protection zones alongside the road, or compensatory protected areas elsewhere to offset the expected road-related natural habitat loss (as is typically required under the World Bank’s Natural Habitats Policy). This kind of mitigation requires effective inter-agency collaboration--for example, between the agencies responsible for roads and protected areas. Direct adverse impacts of road works on biodiversity can also be significant, but they are generally simpler to avoid or mitigate, because they are more fully under the control of road construction agencies, contractors, and concessionaires. Biodiversity loss and environmental damage can be considerably reduced when planners and road construction agencies site roads adjacent to existing railways, pipelines, or transmission lines; practice sound road engineering; maintain good drainage and natural water flows; minimize roadside habitat loss; and, exercise care in the siting and design of borrow pits, construction camps, and other complementary facilities. Environmental rules for contractors, including transparent penalties for noncompliance, need to be incorporated within bidding documents and contracts. Ideally, road projects are designed and implemented so as to avoid or compensate adequately for any adverse impacts on natural habitats and biodiversity. Through mitigation measures such as support for compensatory protected areas, potentially controversial projects can even produce significant net environmental benefits, a win-win outcome.